Nanomundo con Nani y nano (2018)
Nanomundo is a booklet that seeks to teach children and young people the basic principles of nanotechnology. Within its pages, it illustrates with the help of its two characters, Nani and nano, the history, what is it? what is it for? and how is nanotechnology made?